2019
DOI: 10.1177/1526924819835823
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Grounded Theory on Adaptation After Lung Transplantation From Intermediate-Term Patient Experiences

Abstract: Background: Previous research revealed that it is possible for lung recipients to experience health 1 year posttransplant, despite not being fully recovered. However, an in-depth, long-term perspective on how lung recipients' health transition evolves over time is lacking. Thus, the aim of this study was to further develop a grounded theory of health transition by exploring the process of change 1 to 3 years after lung transplantation. Methods: The grounded theory method was used prospectively to analyze the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…They struggled with the “larger size” of pills, and the “avalanche of medicines” taken each day 56 . The burden of the medication regimen and sourcing medications caused some to be “exhausted” and “sick of these pills and fed up.” 21‐25,35,50,55,57,71,82,88,95,100,101,109,121,122 In an attempt to make it palatable, one recipient “told [himself] that these pills are like pieces of chocolate.” 53 Those who struggled to adjust to the new routine felt this contributed to unintentional forgetfulness in taking their medication 24,43,56,57,66,68,89,95,109,113,126 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They struggled with the “larger size” of pills, and the “avalanche of medicines” taken each day 56 . The burden of the medication regimen and sourcing medications caused some to be “exhausted” and “sick of these pills and fed up.” 21‐25,35,50,55,57,71,82,88,95,100,101,109,121,122 In an attempt to make it palatable, one recipient “told [himself] that these pills are like pieces of chocolate.” 53 Those who struggled to adjust to the new routine felt this contributed to unintentional forgetfulness in taking their medication 24,43,56,57,66,68,89,95,109,113,126 …”
Section: Resultsmentioning
confidence: 99%
“…Adjusting to ongoing dependence on medications Some felt transplantation replaced one life with another different set of rules including the routine and regime of taking medications. 23,40,51,56,66,84,93,95,99,103,[120][121][122][123] Although patients often adjusted to the new medication regimens, some found it difficult to adjust and accept the need to take medications. 19,20,21,29,32,33,52,54,57,60,[65][66][67]70,93,94,96,97,102,118,124,125 They struggled with the "larger size" of pills, and the "avalanche of medicines" taken each day.…”
Section: Recalibrating To a New Normal Posttransplantmentioning
confidence: 99%
See 1 more Smart Citation
“…This was somewhat surprising based on our clinical experience where HTRs are often viewed as being in a much better position than LuTRs in terms of survival, complications and the risk of graft rejection. However, previous studies in the SMATT project have revealed a tendency for HTRs to experience more pain than LuTRs [ 32 ] and that LuTRs seem to adapt and manage their symptoms faster than HTRs [ 35 , 36 ]. This highlights the importance of exploring the differences between HTRs and LuTRs to deeper the understanding of the struggles in their respective recovery processes.…”
Section: Discussionmentioning
confidence: 99%
“…Adapting to post-transplant limitations and a changed body is an inherent challenge for HTRs, which is also shown by Lundmark et al [ 24 ] who reported that lung recipients strive to adapt to a new normality by employing strategies such as comparing, accepting and adjusting. There are numerous self-management demands recommended by transplant professionals, e.g., being sufficiently active, adhering to medication and dietary guidelines, protecting oneself from infections and the sun, managing symptoms and mastering one’s role and emotions.…”
Section: Discussionmentioning
confidence: 89%